2021
DOI: 10.3389/fphar.2021.596956
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Ivabradine on Cardiac Vagal Parasympathetic Function in Normal Rats

Abstract: Background: The complex interactions that exist between the pacemaker current, If, and the parasympathetic nervous system could significantly influence the course of patients undergoing chronic therapy with the If blocker ivabradine. We thus aimed to assess the effects of chronic ivabradine therapy on autonomic modulation and on the cardiovascular response to in situ and in vitro parasympathetic stimulation. The right atrial expression of HCN genes, encoding proteins for If, was also evaluated.Methods: Sympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Given that chemogenetic inhibition of glutamate, which is an excitatory neurotransmitter, increased NREM sleep and decreased wakefulness in mice ( Kroeger et al, 2017 ) and more consolidated sleep in zebrafish was observed as a response to a single middle dose of ZD7288 in our study, we suggest that this effect might have been obtained due to inhibition of glutamate release. Although Ivabradine does not cross the blood brain barrier, it inhibits inward current in peripheral and autonomic somatosensory neurons ( Scridon et al, 2021 ), thereby this effect might explain shorter latency to daytime sleep immediately after drug administration. Moreover, HCN channel blocker compounds including Ivabradine ( Demontis et al, 2009 ), Zatebradine hydrochloride ( Satoh and Yamada, 2002 ) and ZD7288 ( Satoh and Yamada, 2000 ) inhibit Ih in HCN channels especially HCN1 in rod photoreceptors which contributes to photoreceptor degeneration ( Schon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that chemogenetic inhibition of glutamate, which is an excitatory neurotransmitter, increased NREM sleep and decreased wakefulness in mice ( Kroeger et al, 2017 ) and more consolidated sleep in zebrafish was observed as a response to a single middle dose of ZD7288 in our study, we suggest that this effect might have been obtained due to inhibition of glutamate release. Although Ivabradine does not cross the blood brain barrier, it inhibits inward current in peripheral and autonomic somatosensory neurons ( Scridon et al, 2021 ), thereby this effect might explain shorter latency to daytime sleep immediately after drug administration. Moreover, HCN channel blocker compounds including Ivabradine ( Demontis et al, 2009 ), Zatebradine hydrochloride ( Satoh and Yamada, 2002 ) and ZD7288 ( Satoh and Yamada, 2000 ) inhibit Ih in HCN channels especially HCN1 in rod photoreceptors which contributes to photoreceptor degeneration ( Schon et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the potential mechanisms contributing to PR prolongation induced by ivabradine include not only the expression of the If channel on the atrioventricular node but also the activation of vagal tone [26]. It is anticipated that these combined factors will exert an influence on the PR interval during the chronic phase following ivabradine administration, thereby contributing to favorable outcomes.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Despite the existing concern, studies including BEAUTIFUL, SIGNIFY, and SHIFT did not show an arrhythmogenic effect [ 93 ]. In addition, some studies suggest that Ivabradine might modulate the vagal effect with the result of preventing atrial arrhythmias [ 94 , 95 ]. Its antiarrhythmic or arrhythmogenic effects await further studies.…”
Section: Future Directionsmentioning
confidence: 99%